Ask Question
6 August, 15:17

Given: F (x) = x + 2 and G (x) = 3x + 5 (F - G) (x) =

1) 4

2) - 3x - 3

3) - 2x - 3

+1
Answers (1)
  1. 6 August, 16:36
    0
    This equation is telling you to subtract the value of f (x) from the value of g (x).

    f (x) = x + 2

    g (x) = 3x + 5

    so x + 2 - 3x - 5 = - 2x-3
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Given: F (x) = x + 2 and G (x) = 3x + 5 (F - G) (x) = 1) 4 2) - 3x - 3 3) - 2x - 3 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers